2017
DOI: 10.1364/ao.56.007549
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between polarimetric and intensity-based surface plasmon resonance sensors in the spectral mode

Abstract: There is a debate on whether phase measurement in surface plasmon resonance (SPR) sensors give better resolution than intensity measurement. In this work, we show that each one of the modes can give better resolution depending on the metal layer thickness chosen, as well as the available noise levels in the system. We propose a three point polarimetric approach to extract the ellipsometric parameters and phase information in the spectral mode. It is shown that the polarimetric measurement at its optimal thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Importantly, the improvement of SPR sensors has progressed with several aims: (1) enhancing the sensitivity; (2) securing selectivity to specific targets; and (3) increasing biocompatible stability. Furthermore, additional advancements in SPR sensors to secure an efficient performance should continue and several research groups proposed SPR sensors with highly improved performances using advanced fabrication and converged techniques, for instance, symmetric insulator-metal-insulator substrate based LRSPR [ 124 ], sensing performance improvement using a top dielectric nanoscale layer [ 124 , 125 ], a spectropolarimetric SPR sensor [ 126 , 127 ], and combined exciting localized and extended surface plasmon sensors with ultrahigh sensitivity [ 128 , 129 ]. On the other direction, the miniaturization of SPR sensors is also needed to increase utilization, and research groups have reported several prototypes of miniaturized SPR sensors [ 130 , 131 , 132 , 133 , 134 , 135 , 136 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the improvement of SPR sensors has progressed with several aims: (1) enhancing the sensitivity; (2) securing selectivity to specific targets; and (3) increasing biocompatible stability. Furthermore, additional advancements in SPR sensors to secure an efficient performance should continue and several research groups proposed SPR sensors with highly improved performances using advanced fabrication and converged techniques, for instance, symmetric insulator-metal-insulator substrate based LRSPR [ 124 ], sensing performance improvement using a top dielectric nanoscale layer [ 124 , 125 ], a spectropolarimetric SPR sensor [ 126 , 127 ], and combined exciting localized and extended surface plasmon sensors with ultrahigh sensitivity [ 128 , 129 ]. On the other direction, the miniaturization of SPR sensors is also needed to increase utilization, and research groups have reported several prototypes of miniaturized SPR sensors [ 130 , 131 , 132 , 133 , 134 , 135 , 136 ].…”
Section: Discussionmentioning
confidence: 99%
“…resolution and high tolerance that depends on the Ag film thickness [89]. CNT/Cu-nanoparticles with good dielectric properties were used for the design of a highly sensitive fiber SPR sensor based on the nanocomposite technique for the sensing of nitrates [90].…”
Section: Specialty Fibersmentioning
confidence: 99%
“…Abbas summarized new sensing materials, such as negative index materials, ZnO, and other analytical techniques combined with SPR, in his review paper [88]. In 2017, Watad et al proposed a spectro-polarimetric SPR sensor with high RI resolution and high tolerance that depends on the Ag film thickness [89]. CNT/Cu-nanoparticles with good dielectric properties were used for the design of a highly sensitive fiber SPR sensor based on the nanocomposite technique for the sensing of nitrates [90].…”
Section: Novel Techniques For Optical Fiber Sensorsmentioning
confidence: 99%
“…In our previous work, the wavelength of incident light was found to affect detection sensitivity in SPR temperature monitoring [ 30 ]. Moreover, SPR phase interrogation at the particular incident wavelength provided a high-resolution angular measurement and other applications [ 31 , 73 , 74 , 75 , 76 , 77 ].…”
Section: Introductionmentioning
confidence: 99%